Infonomics: The Digital Age and prospects of the world economy - Shuren, T.K. ("Акад. Е.А. Бөкетов ат. Қарағанды ун-ті" КЕАҚ баспасы, 2022)
At the present time, when the world economy is experiencing unprecedented crises and collapses of production chains, the primary task for the country's economic security is the availability of a sovereign financial system capable of creating a high-quality national currency and investment capital in volumes that are not inferior to competitors. In this regard, the states in which a full-fledged infonomics will arise, systematically creating information products and intangible assets, will gain competitive advantages, since this will allow them to increase the amount of money created for their support, which is additional energy to accelerate socio-economic development.
Keywords: digital economy; economic growth; the impact of digitalization; multiple regression; correlation